2018
DOI: 10.20506/rst.37.2.2833
|View full text |Cite
|
Sign up to set email alerts
|

Cost–benefit analysis of controlling rabies: placing economics at the heart of rabies control to focus political will

Abstract: Rabies is an economically important zoonosis. This paper describes the extent of the economic impacts of the disease and some of the types of economic analyses used to understand those impacts, as well as the trade-offs between efforts to manage rabies and efforts to eliminate it. In many cases, the elimination of rabies proves more cost-effective over time than the continual administration of postexposure prophylaxis, animal testing and animal vaccination. Economic analyses are used to inform and drive policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Focusing solely on human PEP fails to address the complete epidemiologic picture and will result in the need for never-ending, costly PEP provision. The vaccination of dogs without the expanded provision of PEP to bite victims will eventually eliminate the threat to humans, but would likely result in hundreds of thousands of human deaths as canine vaccination programs are implemented [ 74 ]. Oftentimes, zoonotic disease control efforts are siloed, resulting in unequal control capacities and disease persistence; Gavi is setting a clear example of the importance of recognizing a One Health approach to address rabies control from both a human and animal perspective.…”
Section: Implementing Strong Global Programs For Vaccine Preventable ...mentioning
confidence: 99%
“…Focusing solely on human PEP fails to address the complete epidemiologic picture and will result in the need for never-ending, costly PEP provision. The vaccination of dogs without the expanded provision of PEP to bite victims will eventually eliminate the threat to humans, but would likely result in hundreds of thousands of human deaths as canine vaccination programs are implemented [ 74 ]. Oftentimes, zoonotic disease control efforts are siloed, resulting in unequal control capacities and disease persistence; Gavi is setting a clear example of the importance of recognizing a One Health approach to address rabies control from both a human and animal perspective.…”
Section: Implementing Strong Global Programs For Vaccine Preventable ...mentioning
confidence: 99%
“…Systematic reviews have demonstrated that the per capita investments needed for elimination are comparable to costs identified for the control of malaria and rabies. 5 , 6 Estimated returns for each dollar invested in TB diagnosis and treatment range from US$ 30 to as high as US$ 115, while meeting targets to end the HIV epidemic by 2030 could avoid US$ 24 billion in HIV treatment costs and yield a 15-fold return on countries’ HIV investments. 7 , 8 Elimination of hepatitis B and C through scale-up of new curative therapies for hepatitis C and the highly effective hepatitis B vaccine is also feasible and likely to be cost effective.…”
Section: Background and Context For Disease Eliminationmentioning
confidence: 99%
“…However, vaccination campaigns need to be repeated annually with at least 70% coverage among the susceptible dog population until elimination is achieved 4 7 . Vaccination of humans with exposure to suspected rabid animals (post-exposure prophylaxis, or PEP) is also effective, but it is more expensive than dog vaccination and requires robust surveillance and integration between animal and human healthcare systems 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%